Net2d-LLM: Translating Structured Network Intents into CLI using LLMs with Execution in a Network Digital Twin - Menezes, Jerônimo; Bitzki, Leonardo; Kreutz, Diego (Anais da Escola Regional de Redes de Computadores (ERRC); 2025: Anais da XXII Escola Regional de Redes de Computadores, 2025)
This paper evaluates the use of Large Language Models (LLMs) to translate structured network intents, expressed as Desired State Models (DSMs), into vendor–specific CLI configurations. Net2d–LLM implements a deterministic, single–pass pipeline in which DSMs are rendered into constrained prompts and translated into CLI commands executed within a Network Digital Twin (NDT). The evaluation compares multiple LLMs under identical conditions, using latency, token usage, efficiency, and configuration consistency as assessment dimensions. The results show that general–purpose LLMs, when guided by structured prompts, can reliably generate syntactically valid and functionally correct configurations, demonstrating reproducibility and confirming the feasibility of LLM–driven automation in multivendor network environments.